Relationship Between Type of Treatment And Resilience In Breast Cancer Patients - Fitria, Ria Nur; Ladesvita, Fiora; Komalawati, Dedeh (Universitas Muhammadiyah Surakarta, 2024)
The high number of cancer patients indicates the need for breast cancer disease control. Various types of treatment include surgery, chemotherapy, radiotherapy, and hormone therapy. Good resilience in cancer patients demonstrates their ability to adapt well to the ongoing treatment effects. Resilience refers to an individual's capacity to manage and overcome problems. The purpose of this study is to investigate the connection between different types of treatment and resilience in breast cancer patients. The research employs a quantitative, cross-sectional approach. Sample calculation used the Lemeshow proportion estimation formula, resulting in 112 respondents at RSUP Persahabatan, selected using purposive sampling based on inclusion and exclusion criteria. Respondent characteristics were assessed using observation sheets, and resilience was measured using the Connor-Davidson Resilience Scale 25 (CD-RISC 25) with a Cronbach Alpha reliability coefficient of 0.892. All variables in this study are categorical; thus, chi-square analysis and, for contingency tables larger than 2x2 with predicted frequencies less than 5, Fisher's exact test were applied. Bivariate analysis results showed a significant relationship between the type of treatment and resilience in breast cancer patients, with a p-value of 0.002 (<0.05). Similarly, one of the respondent characteristics based on cancer stage showed a significant relationship with resilience, with a p-value of 0.016 (<0.05). The resilience of breast cancer patients undergoing treatment is very high, at 25.0%.